2016
DOI: 10.1371/journal.pone.0162635
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation and Implementation of Improvement Actions in Butcher Shops

Abstract: Foodborne pathogens can cause acute and chronic diseases and produce a wide range of symptoms. Since the consumption of ground beef is a risk factor for infections with some bacterial pathogens, we performed a comprehensive evaluation of butcher shops, implemented improvement actions for both butcher shops and consumers, and verified the impact of those actions implemented. A comprehensive evaluation was made and risk was quantified on a 1–100 scale as high-risk (1–40), moderate-risk (41–70) or low-risk (71–10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
25
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 41 publications
5
25
0
5
Order By: Relevance
“…In the US, non-O157 STEC prevalence was 9.4% in retail beef [ 43 ] and 6.6, 1.8, 4.6 and 20.3% in domestic and imported beef trimmings from New Zealand, Australia and Uruguay, respectively [ 44 ]. Our findings were similar to those reported by Bosilevac et al [ 44 ] in beef trimmings, and also agree with the previously reported low prevalence (0.6%) of top six STEC in Argentina identifying only one O26 STEC from retail raw ground beef [ 45 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the US, non-O157 STEC prevalence was 9.4% in retail beef [ 43 ] and 6.6, 1.8, 4.6 and 20.3% in domestic and imported beef trimmings from New Zealand, Australia and Uruguay, respectively [ 44 ]. Our findings were similar to those reported by Bosilevac et al [ 44 ] in beef trimmings, and also agree with the previously reported low prevalence (0.6%) of top six STEC in Argentina identifying only one O26 STEC from retail raw ground beef [ 45 ].…”
Section: Discussionsupporting
confidence: 93%
“…Some of the serotypes found in this study (O8:H19, O91:H21, O113:H21, O130:H11, O174:H21 and O178:H19) have been previously isolated from cattle, food and the environment in Argentina [ 46 ]. O8:H19, O174:H21 and O178:H19 were the most frequently found; they were isolated from all types of sources and associated with at least one HUS case in Argentina [ 45 , 47 – 49 ]. However, none were associated with HUS during our study period according the Argentinean surveillance system [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intervention strategies to avoid the contamination of meat products and consequently, to reduce the STEC incidence in humans, have been focused on live cattle on the farm, on slaughter plants, and on the final product at retail (Brashears & Chaves, ; Leotta et al, ). The National Service of Agrifood Health and Quality of Argentina (SENASA, for its Spanish acronym) applies intervention measures in order to reduce these bacteria on carcasses (SENASA, ).…”
Section: Discussionmentioning
confidence: 99%
“…monocytogenes can multiply at refrigeration temperatures, form biofilms on different materials and under various conditions, and resist a range of environmental stresses (Law et al, 2015). Thus, the presence of this bacterium in retail shop environments is a risk due to the possibility of crosscontamination with food products (Leotta et al, 2016). We, therefore, conducted a field study to apply and validate the RT-PCR developed.…”
mentioning
confidence: 99%